Pemberdayaan Masyarakat melalui Pendidikan Keluarga dalam Membangun Karakter Anak di Era Society 5.0 di Kecamatan Sirimau, Kota Ambon - Kundre, Junita Liliana; Abarua, Hermelina; Suripatt, Garace (Universitas Pattimura, 2025)
This community service was conducted to address the low public awareness in Sirimau District regarding the importance of family education in shaping children’s character in the Society 5.0 era. The goal was to enhance parents’ and early childhood educators’ ability to integrate character values and digital literacy in child upbringing. The program applied a participatory approach through counseling, training, and community-based mentoring. Results revealed significant improvement in parents’ understanding and skills in guiding children to use technology wisely, as well as the establishment of family learning groups for continuous character education. The program strengthened collaboration between families, educational institutions, and local government to create a supportive social environment for children’s development. It implies that sustainable family education initiatives require consistent policy support and community facilitation.